Performance evaluation of a desiccant-evaporative cooling air-conditioning system - Thom, Martin Gunther (My University, 1998)
The main objective of this project was to evaluate the performance of a desiccant evaporative cooling (DEC) system operating in the ventilation (once-through) mode. An accurate data acquisition system was installed on a small DEC test installation located in the School of Mechanical Engineering, University of the Witwatersrand, Johannesburg. The DEC system was extensively tested to fully evaluate the overall system and each of its components. (Abbreviation abstract)
A project report submitted to the Faculty of Egineering, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Engineering.
Keywords: Air conditioning.; Evaporative cooling.; Ventilation.